2015
DOI: 10.1080/07315724.2014.926162
|View full text |Cite
|
Sign up to set email alerts
|

Profile Development of Noncommunicable Chronic Diseases in a Brazilian Rural Town

Abstract: Our results indicate that the studied population is affected by nutritional transition, in which the greater access to carbohydrates and animal proteins is associated with high BMI, with the vast majority overweight and suffering from uncontrolled hypertension despite the use of medications. The high consumption of carbohydrates and animal protein, rapid urbanization, and sedentary lifestyle are the main factors responsible for the epidemic of noncommunicable diseases, especially among people with low income a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Vector is a set of mediating variables, whose risk level differences among participants were potentially posed by urban-rural living disparity, including BMI, frequency of dining out, sedentary time, and psychological distress. is control variable vector including gender, age, marital status, and smoking habits ( 19 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vector is a set of mediating variables, whose risk level differences among participants were potentially posed by urban-rural living disparity, including BMI, frequency of dining out, sedentary time, and psychological distress. is control variable vector including gender, age, marital status, and smoking habits ( 19 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…We adopted a broader range of potential mediators from the literature and make the contributions between risk factors comparable. Second, some previous studies were based on a set of cross-sectional data ( 19 21 ). This approach can observe the effect at a particular period, while it may ignore capturing the long-term trends; hence, we provided a longitudinal analysis using data from different time points and classified the impact of urban living on different types of chronic diseases, in an effort to develop a more targeted prevention and control system for chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Junto con la subalimentación y la malnutrición, las ECNT se ubican entre las principales causas de muerte en los países de la región, entre ellas las enfermedades cardiovasculares, la diabetes y el cáncer [14][15][16][17] . Se ha descrito que el sobrepeso y la obesidad son factores de riesgo para el desarrollo de ECNT 14 .…”
Section: Beneficios Nutricionales Agroecológicos Y Comerciales De Launclassified
“…Concomitantly, it was possible to observe profound changes in the behavior and eating habits of families around the world ( Popkin, 2015 ). Higher levels of undernutrition have been replaced by higher rates of overweight and obesity related to hyperlipidic and hypercaloric food consumption ( Di Pietro et al, 2015 ). Epidemiological evidence has shown that nutritional deficiency in the first years of life accompanied by overnutrition, a posteriori , may increase the risk of dyslipidemia and other cardiometabolic diseases in adulthood, such as hypertension and type 2 diabetes ( Figure 1 ) ( Barker, 2007 ).…”
Section: Introductionmentioning
confidence: 99%